WEB-BASED FOOD ORDERING TRANSFORMATION WITH CONTROLLING MANAGEMENT FUNCTIONS - Rouf, Muhammad Zainur; Supriyanto, Supriyanto; Arsandi, M Rias; Setiani, Setiani Husnul (Proceedings of the International Conference of Islamic Economics and Business (ICONIES), 2022)
The ordering process is something that supports the quality of service in a place to eat or a restaurant. We know a lot in the ordering process that places to eat are used manually (must write in inputting orders) so that it requires transformation to keep up with the times. Mbak Yuyun's stall, which is located in Malang City, Mbak Yuyun Is the name of a bamboo stall that is the location or object for research. still uses a manual system in its service, so that a problem arises, namely a very long queue that will trigger the loss of taste or interest in the purchasing power of consumers in the shop. In addition, there is a double order problem so that the order is often out of order when the waiter delivers the food. Therefore, in this study, an online website was created via a smartphone by scanning the barcodes available at each dining table. In addition, it is not only the website, but the researchers will also implement other elements, namely the controlling management function so that over time this website will continue to be monitored. The method that the researcher uses is descriptive qualitative which is deductive in nature. And the results of this study are that almost 60% of the answers to the questionnaire have agreed and supported the existence of this Marwan Click the website.